Long-term outcomes after endoscopic ultrasound-guided ablation of pancreatic cysts - Choi, Jun-Ho; Seo, Dong Wan; Song, Tae Jun; Park, Do Hyun; Lee, Sang Soo; Lee, Sung Koo; Kim, Myung-Hwan (Endoscopy, 2017)
Background and study aims The aim of this study was to investigate the long-term outcomes after endoscopic ultrasound (EUS)-guided pancreatic cyst ablation. Patients and methods In a single-center, prospective study, 164 patients with pancreatic cysts underwent EUS-guided cyst ablation using ethanol with paclitaxel. The inclusion criteria were as follows: unilocular or oligolocular cysts; clinically indeterminate cysts that required EUS fine-needle aspiration; and/or cysts that grew during the observation period. Treatment response was classified as complete resolution, partial resolution, or persistent cyst, with < 5 %, 5 % – 25 %, and 25 % of the original cyst volume, respectively.Results The median largest diameter of the cyst was 32 mm and the median volume was 17.1 mL. Based on cyst fluid analysis there were 71 mucinous cystic neoplasms, 16 serous cystic neoplasms, 11 intraductal papillary mucinous neoplasms, 3 pseudocysts, and 63 indeterminate cysts. Sixteen treated patients (9.8 %) had adverse events (1 severe, 4 moderate, and 11 mild). Treatment response was as follows: complete resolution in 114 (72.2 %), partial resolution in 31 (19.6 %), and persistent cysts in 13 (8.2 %). Twelve of the 13 patients with persistent cysts underwent surgery. During clinical and imaging follow-up (median 72 months, interquartile range 50 – 85 months) of the 114 patients with complete resolution, only two patients (1.7 %) showed cyst recurrence. Based on multivariate analysis, the absence of septa (odds ratio [OR] 7.12, 95 % confidence interval [CI] 2.72 – 18.67) and cyst size less than 35 mm (OR 2.39, 95 %CI 1.11 – 5.16) predicted complete resolution.Conclusion Among patients with pancreatic cysts in whom complete resolution was achieved after EUS-guided cyst ablation, 98.3 % remained in remission at 6-year follow-up. Unilocular form and small cyst size were predictive of complete resolution. This treatment approach may be an effective and durable alternative to surgery.Trial registered at ClinicalTrials.gov (NCT 00689715).